(untitled) (Jurnal Wahana Konseling, 2024)
Finding out how accepting domestic abuse victims are of themselves is the goal of this study conducted at the SPEK-HAM Surakarta Foundation. This study takes a phenomenological perspective while using a qualitative research methodology. The research subjects were two people with the following criteria: 1) Domestic violence victims aged 40-45 years, 2) Domestic violence victims who had been divorced for 5-10 years, 3) Domestic violence victims who had participated and received assistance at the Surakarta SPEK-HAM Foundation. Documentation, semi-structured interviews, and observation are the methods used to acquire research data. According to the study’s findings, both participants exhibited high levels of self-acceptance. Both participants recovered with positive development and a healthy sense of self-acceptance, despite the fact that they underwent a very drawn-out procedure.